Performance Analysis of Sulphur Infiltrated-Concrete (SIC): A Novel Approach for Strength Improvement - Pathak, Gayatri; Mishra, S. Sangita; Charhate, Shrikant (Engineering, Technology & Applied Science Research, 2026)
The growing demand for concrete due to rapid urbanization necessitates large-scale cement production, contributing significantly to CO₂ emissions. As a sustainable alternative, Sulphur-Infiltrated Concrete (SIC) utilizes molten sulphur, an oil and petroleum industry by-product, to fill voids in porous concrete. This study explores the potential of SIC, focusing on its production process, mix design, mechanical performance, and microstructural characterization. Concrete specimens (150×150×150 mm cubes) with varying water-cement (w/c) ratios (0.50-0.70) and cement contents (235.71-330 kg/m³) were infiltrated with 99% pure molten sulphur at 140 °C. Experimental trials evaluated compressive strength using destructive and non-destructive methods, including Rebound Hammer and Ultrasonic Pulse Velocity (UPV) tests. Microstructural analysis was conducted using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) at 1-day and 7-day curing periods. Durability was assessed through carbonation testing and water absorption studies. The results showed increased early compressive strength, even with reduced cement content, with Trial 3 (w/c = 0.70) demonstrating superior performance due to enhanced sulphur penetration. Microscopic analysis revealed reduced porosity and improved bonding between sulphur and cement matrix. Water absorption tests indicated minimal absorption, confirming enhanced impermeability. Cost-benefit analysis indicates long-term economic viability. SIC demonstrates promise as an eco-friendly alternative for precast construction applications, offering dual benefits of waste utilization and reduced cement consumption.